Two new cases of gynandromorphism in Xylocopinae bees (Hymenoptera: Apidae) from India. (3rd April 2019) - Prashantha, Chikkabuddi; Lucia, Mariano; Belavadi, Vasuski V.
ABSTRACT: Two new cases of gynandromorphs in carpenter bees are described and illustrated for the first time in Ceratina ( Pithitis ) binghami Cockerell and Xylocopa ( Biluna ) nasalis Westwood. The gynandromorphs described herein belong to the mixed or mosaic category of gynandromorphs because they exhibit a mixture of male and female features only in the head region.